Utilizing Sediment Microbial Fuel Cells (SMFCs) for Bioremediation in Coral Transplantation at Samalona Island - Sri Magfirah HS; Surya Dharma; Mudasir Zainuddin (ARRUS Journal of Engineering and Technology, 2024)
This study explores the potential of Sediment Microbial Fuel Cells (SMFCs) in the bioremediation of coral transplantation environments at Coral Garden Samalona, Samalona Island, Makassar. An experimental approach using marine aquariums was employed to assess the effects of SMFCs on the coral environment. Physicochemical parameters such as temperature, pH, salinity, and total dissolved solids (TDS) were monitored in real time using IoT technology. Statistical analysis using the Mann-Whitney test revealed significant effects of SMFCs on these parameters, with Asymp. Sig (2-tailed) < 0.05, revealing positive changes. The pH remained stable in an alkaline range (8.16-8.36), while TDS and salinity decreased by 3.19% and 15%, respectively. However, challenges related to temperature fluctuations in the SMFC group, likely due to microbial activity, were noted, as evidenced by peak voltage outputs ranging from 84.3 to 96.6 mV. Although this voltage remains low for broader applications, further research is needed to address temperature fluctuations, increase voltage output, and optimize SMFC design for real-world implementation.